Design Planning of Small Dam Conservation at Deer Park University of Lampung - Wahyuni, Nining; Taufik Purwadi, Ofik; Sumiharni, Sumiharni (Universitas Lampung, 2019)
In the Faculty of Medicine, University of Lampung there is a pool with a small reservoir that can overflow during the rainy season, because it has not been able to accommodate the inflow water. The solution is planning a small dam to increase its function as water reservoir, flood control, and conservation.The methods are used to redesign this small dam conservation are hydrological analyses, small dam construction planning, analysis stability of planned constructions and estimating building construction cost. The result are storage capacity of small dam is 3627,9560 m3 from storage capacity before redesign is 3219,7176 m3, the flood debit of 0,8219 m3/s with cycle period 5 years, small dam planned height of 4,5 m,withabaseelevationat+103,5 thedamcrestelevation+106,61. Spillway which used is Open Ogee type and basin specific energy building Vlughter type. Stability small dam construction stated as safe with flood condition, normal condition and empty condition. Cost estimated of design planning of conservation small dam at Medicine Faculty University of Lampung is Rp3.265.660.000. (three billion two hundred sixty five million hundred sixty thousand Rupiah). Keyword : Small dam, Conservation, University of Lampung